OP0051 Differential Methylation Related to Response to Etanercept in Patients with Rheumatoid Arthritis. (23rd January 2014) - Webster, A.; Plant, D.; Eyre, S.; Flynn, E.; Martin, P.; Wilson, G.; Morgan, A. W.; Isaacs, J.; Worthington, J.; Barton, A.
Abstract : Background: The introduction of biologic drug therapies targeting specific components of the inflammatory response represents a huge advance in the treatment of rheumatoid arthritis (RA). Despite this, up to 40% of patients fail to respond well to these therapies. Ideally, clinicians would like to identify patients who are likely to respond to therapy as early as possible in the disease course, making identification of reliable biomarkers of response an important area of research. Recent studies suggest that epigenetic control of gene expression may be important in RA, we have therefore hypothesized that epigenetic changes such as methylation may provide useful biomarkers of response to biologics. Objectives: To identify a methylation signature indicative of response to TNF-blockade therapy in patients with RA. Methods: Patients were recruited from the Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate (BRAGGSS) longitudinal cohort. Patients (n=24) were selected based on having an extreme response phenotype after 3 months of treatment with etanercept; 12 were good responders defined as having an endpoint DAS28<2.6, and 12 were poor responders defined as having an improvement of <0.6 or between 0.6-1.2 with an endpoint DAS28 of >5.1. DNA from each patient, sampled before initiation of etanercept therapy, was bisulfite converted and an epigenome wide association study was conducted using the HumanMethylation450 BeadChip (Illumina). The results were then analysed using the minfi package in R. A detection threshold was applied and probes with a detection p-value of greater than 0.01 were removed. Differentially methylated positions between responders and non responders were identified using the F-test following quantile normalisation. Results: The fraction of failed probes per sample was less than 0.5%. 9 probes showed significant differences between responders and non-responders to etanercept (p≤10 -4 ): cg01037362, cg24725337, cg23704085, cg18631743, cg01379412, cg23881368, cg00011856, cg26282792, cg18772588. Interestingly, cg00011856 (p=9.46x10 -5 ) maps 1500bp upstream of the transcription start site of the IGFBP5 gene, a known inhibitor of TNF-TNFR1 interactions. The mean beta value for methylation at this CpG site was 0.40 for responders and 0.50 for non-responders. Conclusions: This is the first methylome wide investigation of treatment response to TNF blockade therapy in RA and, while further well powered studies are required, these preliminary data indicate a possible methylation biomarker of response. Acknowledgements: This work was supported by the innovative medicines initiative joint undertaking (IMI JU) funded project BeTheCure, (contract number 115142-2). Disclosure of Interest: None Declared